Development Of Social Capital In Urban Farming-Based Farmer Groups In Rw 03, Cempaka Putih Timur Village, Central Jakarta - Kamelia Sambas; Robert Markus Zaka Lawang (Al-Makki Publisher, 2023)
This research discusses the development of social capital for farmer groups based on urban farming in RW 03 Cempaka Putih Timur. This research aims to describe the process of developing bonding social capital of farmer groups, the benefits of bonding in building bonding relationships with consumers, and linking social capital to the government or companies. This research uses a qualitative approach with a descriptive design, by conducting observations and in-depth interviews with 25 informants selected using a purposive sampling technique. The results of this research show that the process of developing bonding social capital describes the relationship between farmer groups and their members which begins with the existence of common goals and relationships between members of the farmer group who have emotional closeness. Bridging the social capital of the farmer group describes the relationship between the farmer group and the RW 03 community, non-members of the farmer group, visiting guests, assisted groups, and people outside RW 03 who are consumers. Linking social capital describes relations with local governments, LH Sub-Department, KPKP Sub-department, Companies, Districts, Villages, Rukun Warga (RW) and Rukun Tetangga (RT). Forms of social capital in farmer groups are strengthened by networks that arise from trust so that the exchange of needed resources occurs. Obligations and expectations as well as norms support bonding social capital in strengthening relationships between farmer groups. Positive sanctions support linking social capital by providing rewards that can increase the motivation and commitment of farmer group members.